Teacher Readiness in Developing Teaching Modules Based on Local Wisdom: A Case Study of Junior High School Teachers in Magetan District - Shodikin, Ali; Susanah, Susanah; Masriyah, Masriyah (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2024)
Teacher readiness in planning learning is an important element of teacher success in achieving learning goals. In the Merdeka Curriculum, this learning plan is realized in the form of teaching modules, one of the approaches of which can be directed at local wisdom. The purpose of this article is to describe teachers' readiness in developing mathematics teaching modules based on local wisdom. A case study of teacher readiness was conducted on 21 junior high school mathematics teachers in Magetan Regency who came from different schools during teacher training which was measured through understanding before and after training as well as the resulting teaching module products. The research results show that the level of teacher readiness in developing teaching modules has reached the criteria of proficient to proficient after receiving training and there has been an increase compared to the previous situation. However, some teachers still have difficulty in developing learning objectives and developing problems based on local wisdom. Several challenges in developing this teaching module have also been identified and several alternative solutions have been explained.